The Effect of Dissimilatory Manganese Reduction on Lactate Fermentation and Microbial Community Assembly - Novotnik, Breda; Zorz, Jackie; Bryant, Steven; Strous, Marc (Frontiers in Microbiology, 2019)
Fermentation and dissimilatory manganese (Mn) reduction are inter-related metabolic processes that microbes can perform in anoxic environments. Fermentation is less energetically favourable and is often not considered to compete for organic carbon with dissimilatory metal reduction. Therefore, the aim of our study was to investigate the outcome of the competition for lactate between fermentation and Mn oxide (birnessite) reduction in a mixed microbial community. A birnessite reducing enrichment culture was obtained from activated sludge with lactate and birnessite as the substrates. This enrichment was further used to test how various birnessite activities (0 mM, 10 mM, 20 mM, and 40 mM) affected the rates of fermentation and metal reduction, as well as community composition. Increased birnessite activity led to a decrease of lactate consumption rate. Acetate and propionate were the main products. With increasing birnessite activity, the propionate/acetate ratio decreased from 1.4 to 0.47. Significant CO2 production was detected only in the absence of birnessite. In its presence, CO2 concentrations remained close to the background since most of the CO2 produced in these experiments was recovered as MnCO3. The Mn reduction efficiency (Mn(II) released/added birnessite) was the highest at 10 mM birnessite added, where about 50% of added birnessite was reduced to Mn(II), whereas at 20 mM and 40 mM approximately 21% and 16 % was reduced. The decreased birnessite reduction efficiency at higher birnessite activities indicates inhibition by terminal acceptors and/or its toxicity which was also indicated by lactate oxidation results. Birnessite activity strongly affected microbial community structure. Firmicutes and Bacteroidetes were the most abundant phyla at 0 mM of birnessite. Their abundance decreased with increasing birnessite concentration. The relative sequence abundance of Proteobacteria increased with increasing birnessite concentrations. Most of the enriched populations were involved in lactate/acetate or amino acid fermentation and the only previously known metal reducing genus detected was related to Shewanella sp. The sequencing data confirmed that lactate consumption coupled to metal reduction was only one of the processes occurring and did not outcompete fermentation processes.